A CASE REPORT OF SHARED PSYCHOTIC DISORDER OR ‘FOLIE A FAMILLE’ AMONGST FOUR FAMILY MEMBERS - Saravanan Kathiresan; Nur Salsabella Asmuni; Ahmad Izzat Ahmad Tajjudin; Hajar Mohd Salleh Sahimi (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Shared psychotic disorder is a common condition and there are many subtypes of this condition. Of these subtypes, only a small percentage involves families. In previous versions of the ‘Diagnostic and Statistical Manual of Mental Disorders (DSM), this was popularly known as ‘Folie a Deux’ (Srivatsava and Borkar, 2010). In the latest DSM-5 version, this diagnosis has been removed and grouped under the umbrella of ‘Delusional Disorders’ owing to the fact that the belief in question might normally be widely shared amongst people of the same culture (DSM 5, 2013). In ICD-10 diagnostic codes however, ‘Shared Psychotic Disorder’ still remains relevant. Folie a Famille (sub-classification of ‘folie a deux’) is characterized by two or more members within a family sharing the same delusion. We report a case of 4 family members who shared the same spiritually themed delusions. Shared Psychotic Disorder is commonly managed by separating the index case from other family member (s) and treatment with antipsychotic medication.